Psychological Treatments for Borderline Personality Disorder: A Review of Cognitive-Behavioral Oriented Therapies - Marques, Sofia (2017)
Introduction: Borderline personality disorder is the most common personality disorder, with a global prevalence rate between 1.6% and 6%. It is characterized by affective disturbance and impulsivity, which lead to a high number of self-harm behaviors and great amount of health services use. International guidelines recommend psychotherapy as the primary treatment for borderline personality disorder. This paper reviews evidence about the effects and efficacy of cognitive-behavioral oriented psychological treatments for borderline personality disorder.Material and Methods: A literature review was conducted in Medline and PubMed databases, using the following keywords: borderline personality disorder, cognitive-behavioral psychotherapy and efficacy.Results: Sixteen randomized clinical trials were evaluate in this review, which analyzed the effects of several cognitive-behavioral oriented psychotherapeutic interventions, namely dialectical behavioral therapy, cognitive behavioral therapy, schema-focused therapy and manual-assisted cognitive therapy. All above stated treatments showed clinical beneficial effects, by reducing borderline personality disorder core pathology and associated general psychopathology, as well as by reducing the severity and frequency of self-harm behaviors, and by improving the overall social, interpersonal and global adjustment. Dialectical behavioral therapy and schema-focused therapy also caused a soaring remission rate of diagnostic borderline personality disorder criteria of 57% and 94%, respectively.Discussion: Although there were differences between the psychotherapeutic interventions analysed in this review, all showed clinical benefits in the treatment of borderline personality disorder. Dialectical behavioral therapy and schema-focused therapy presented the strongest scientific data documenting their efficacy, but both interventions are integrative cognitive-behavioral therapies which deviate from the traditional cognitive-behavioral model.Conclusion: In summary, the available studies support cognitive-behavioral psychological treatments as an efficacious intervention in borderline personality disorder. However, the existing scientific literature on this topic is still scarce and there is need for more studies, with higher methodological rigor, that should validate these results.